Attitudes towards autonomous vehicles among people with physical disabilities. (September 2019) - Bennett, Roger; Vijaygopal, Rohini; Kottasz, Rita
Highlights: Examines the views of a sample of people with physical disabilities regarding autonomous vehicles (AVs). Determines attitudes towards AVs using a semi-automated qualitative research methodology. Compares the views of people with disabilities against a control group of people without disabilities. Suggests topics for inclusion in social marketing AV acceptance campaigns. Identifies variables likely to affect the attitudes of people with disabilities towards AVs. Abstract: Autonomous vehicles (AVs) represent a technological revolution in the transportation sphere. The efficient and orderly introduction of AVs will require their acceptance by the public. Although the perspectives of members of the general public concerning AVs have been surveyed, no academic research has to date been completed on the views of AVs held by people with disabilities. The present study employs a mixed methods research methodology to assess attitudes towards AVs among a UK sample of individuals with physical disabilities that affected their mobility. Participants were asked open-endedly to express their thoughts about AVs and their responses were analysed using a structural topic modelling (STM) procedure. Outputs to the STM analysis were then employed in a structural equation model (SEM) constructed to predict the sample members' willingness to travel in driverless vehicles. The results were compared against those obtained from a control group of people without physical disabilities. The attitudes towards AVs of people with disabilities differed significantly from the attitudes of the respondents without disabilities. Attitudes towards AVs among people with disabilities were significantly influenced by their levels of interest in new technology, generalised anxiety, intensity of a person's disability, prior knowledge of AVs, locus of control and action orientation. A latent class analysis confirmed the relevance of these variables as determinants of the views of people with disabilities regarding AVs.